Thermodynamic analysis of expansion process of screw expander in wet steam area - A. M. Kalashnikov; G. I. Chernov; V. L. Yusha (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In this scientific work, the process of expansion of wet steam with different values of the inlet degree of dryness in a screw expander is considered. The study is carried out on the basis of the developed mathematical model, which includes both the basic thermodynamic equations and the process of heat exchange of the working substance with the environment in the process of expansion. During the study of the expansion process in the area of wet steam in a screw expander, a mathematical model of this process is developed. The mathematical model is verified by comparing the results obtained on its basis with the results obtained by other researchers on an identical object. It can be seen from the results obtained that at values of the initial degree of dryness greater than 0,01, the distributions of pressures and temperatures practically do not depend on its value. When the initial dryness values are less than 0,01, it begins to have a significant effect on the distribution of pressure and temperature over the angle of rotation of the main rotor of the screw expander.